The Effect of Profitability, Leverage, and Company Size on Tax Avoidance in Property and Real Estate Companies Listed on The Indonesia Stock Exchange for The Period 2020 - 2024 - Angelia Santika Naisau; Cakti Indra Gunawan; As’adi; Risnaningsih (International Journal of Management and Business, 2026)
The property and real estate sector in Indonesia makes a significant contribution to national economic growth, yet increasingly complex tax avoidance practices pose challenges to state revenue.. This study aims to examine the effect of profitability, leverage, and firm size on tax avoidance in property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. The research method employed is a quantitative approach using multiple linear regression analysis with SPSS. A sample of 20 companies was selected using purposive sampling from a population of 93 property and real estate companies, yielding 76 observations after outlier elimination. Profitability is measured by Return on Assets (ROA), leverage by Debt to Equity Ratio (DER), firm size by the natural logarithm of total assets, and tax avoidance by the Effective Tax Rate (ETR). The results indicate that: (1) profitability has a significant negative effect on tax avoidance (t = -1.955; sig. 0.044); (2) leverage has a significant positive effect on tax avoidance (t = 2.608; sig. 0.011); (3) firm size has a significant negative effect on tax avoidance (t = -2.897; sig. 0.005); (4) simultaneously, the three variables significantly influence tax avoidance (F = 5.799; sig. 0.001), explaining 48.5% of its variation.